A Preliminary Experimental Examination of the Effect of Emotion Dysregulation and Impulsivity on Risky Behaviors Among Women With Sexual Assault–Related Posttraumatic Stress Disorder. (November 2014) - Weiss, Nicole H.; Tull, Matthew T.; Gratz, Kim L.
Posttraumatic stress disorder (PTSD) is associated with a wide range of risky behaviors (e.g., substance use and risky sexual behaviors); however, few studies have examined mechanisms that may underlie risky behaviors in this population. The present study utilized a prospective experimental design to examine the effects of emotion dysregulation and impulsivity on risky behaviors across time. Thirty women with sexual assault–related PTSD were randomly assigned to receive emotion modulation (EM), impulsivity reduction (IR), or healthy living (HL; comparison condition) skills trainings. Participants completed measures of emotion dysregulation, impulsivity, and risky behaviors pre-manipulation and 1-month post-manipulation. Participants in the EM and IR conditions reported a significant reduction in risky behaviors from pre- to post-manipulation relative to the HL condition. Changes in emotion dysregulation from pre- to post-manipulation fully accounted for reductions in risky behaviors over time. Results provide preliminary experimental support for the role of emotion dysregulation in risky behaviors.